2011
DOI: 10.1002/lary.22140
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem response morphology and analysis in very preterm neonatal intensive care unit infants

Abstract: A typical bow tie pattern preceding peak III seems to be the earliest characteristic of the developing ABR morphology in preterm infants. As ABR characteristics will improve with increasing age, neonatal hearing screening should be postponed until after 34 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Auditory brainstem response (ABR) was considered as a potential method and was therefore explored in several studies. In a vast majority of infants even born at 26 weeks of gestation, an auditory signal could be detected in the developing brain (Coenraad et al 2011b). Also, differences in aetiologic factors could be seen distinguishing between infants with certain diseases and without these diseases (Coenraad et al 2011a).…”
Section: Sound Designmentioning
confidence: 99%
“…Auditory brainstem response (ABR) was considered as a potential method and was therefore explored in several studies. In a vast majority of infants even born at 26 weeks of gestation, an auditory signal could be detected in the developing brain (Coenraad et al 2011b). Also, differences in aetiologic factors could be seen distinguishing between infants with certain diseases and without these diseases (Coenraad et al 2011a).…”
Section: Sound Designmentioning
confidence: 99%
“…Between 24 and 42 h of age, failure on 1st OAE failed was twice more among LP than full-term infants. This is probably due to younger GA of the LP infants and is possibly related the known delayed maturation of the hearing system after birth in premature infants [3,8,18,19]. GA of 35⁰-37 6 weeks should be included among the risk factors for failure on 1st OAE.…”
Section: Discussionmentioning
confidence: 99%
“…Sleifer et al [18], Casali and Santos [3] and Coenraad et al [19] performed auditory brainstem response (ABR) tests in neonates and found that maturation of the hearing system after birth in term infants differs significantly from that in premature infants. This led to the recommendation to screen premature infants only after 34 weeks' postmenstrual age [19]. Weichbold et al [8] also showed that prematurity <33 weeks is a significant risk factor for hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the ABR in premature [ 87 ]. The greatest change in latencies and amplitudes comes after birth.…”
Section: Eeg and Amplitude-integrated Eeg (Aeeg)mentioning
confidence: 99%